Konsep Pemasaran Untuk Usaha Baru Hidroponik Titik Tanam Minimum - Ema Nurzainul Hakimah (Fakultas Ekonomi Universitas Kadiri, 2019)
This research activity is motivated by the lack of optimal marketing of hydroponic products produced by PKM partner, PKM Program of Kemenristek Dikti Grant 2017, Pokja 4 TPPKK and Menur Posyandu, Blabak Village, Pesantren District, Kediri City, East Java Province. The success of hydroponic cultivation has not been followed by the ability to market. The accuracy of the marketing concept is expected to be able to maximize profits, when pranoto mongso consept in the limited land, and the minimum planting point can be done by partners. Based on this background, the formulation of the problem in this study is